Food packaging cues influence taste perception and increase effort provision for a recommended snack product in children - Enax, Laura; Weber, Bernd; Ahlers, Maren; Kaiser, Ulrike; Diethelm, Katharina; Holtkamp, Dominik; Faupel, Ulya; Holzmüller, Hartmut H.; Kersting, Mathilde (Frontiers in Psychology, 2015)
Food marketing research shows that child-directed marketing cues have pronounced effects on food preferences and consumption, but are most often placed on products with low nutritional quality. Effects of child-directed marketing strategies for healthy food products remain to be studied in more detail. Previous research suggests that effort provision explains additional variance in food choice. This study investigated the effects of packaging cues on explicit preferences and effort provision for healthy food items in elementary school children. Each of 179 children rated three, objectively identical, recommended yoghurt-cereal-fruit snacks presented with different packaging cues. Packaging cues included a plain label, a label focusing on health aspects of the product, and a label that additionally included unknown cartoon characters. The children were asked to state the subjective taste-pleasantness of the respective food items. We also used a novel approach to measure effort provision for food items in children, namely handgrip strength. Results show that packaging cues significantly induce a taste-placebo effect in 88% of the children, i.e., differences in taste ratings for objectively identical products. Taste ratings were highest for the child-directed product that included cartoon characters. Also, applied effort to receive the child-directed product was significantly higher. Our results confirm the positive effect of child-directed marketing strategies also for healthy snack food products. Using handgrip strength as a measure to determine the amount of effort children are willing to provide for a product may explain additional variance in food choice and might prove to be a promising additional research tool for field studies and the assessment of public policy interventions.